2014
DOI: 10.1007/s00262-013-1515-6
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic blebs from leukemic cells as a preferred source of tumor-associated antigen for dendritic cell-based vaccines

Abstract: Since few leukemia-associated antigens (LAA) are characterized for acute myeloid leukemia (AML), apoptotic tumor cells constitute an attractive LAA source for DC-based vaccines, as they contain both characterized and unknown LAA. However, loading DC with apoptotic tumor cells may interfere with DC function. Previously, it was shown in mice that apoptotic blebs induce DC maturation, whereas apoptotic cell remnants (ACR) do not. Here, we analyzed human monocyte-derived DC (MoDC) functionality in vitro, after ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…By co-administering immunostimulatory agents (e.g., 4/GM, CpG, and TLR ligands) tumor-enforced immunosuppression may be counteracted and the T cell stimulatory capacity of skin DCs greatly enhanced. 11,12,27,46 The data presented here, combined with our previous data, 22 present a strong case for the use of blebs as potent source of TAAs for the induction of tumor-directed immunity through dermally applied vaccines.…”
Section: 1332mentioning
confidence: 69%
See 2 more Smart Citations
“…By co-administering immunostimulatory agents (e.g., 4/GM, CpG, and TLR ligands) tumor-enforced immunosuppression may be counteracted and the T cell stimulatory capacity of skin DCs greatly enhanced. 11,12,27,46 The data presented here, combined with our previous data, 22 present a strong case for the use of blebs as potent source of TAAs for the induction of tumor-directed immunity through dermally applied vaccines.…”
Section: 1332mentioning
confidence: 69%
“…29 Previously, we reported on apoptotic cell-derived blebs as a potent source of TAAs for ex vivo generated DC-based vaccines. 22 Here, we used a human skin explant model to explore the relative efficiency of loading skin resident DCs with either ACRs or blebs in situ as a tumor cell-based vaccine delivery method. We found i.d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, using tumor cells or tumor 742 cell elements as antigen source entails the risk of delivering other tumor-derived factors that have immunosuppressive effects (e.g., IL-10 and transforming growth factor-b) (Schui et al, 2002;Schottker and Schmidt-Wolf, 2011;Szczepanski et al, 2011;Ruben et al, 2013;Hong et al, 2014). Nevertheless, several studies have shown that an effective CTL immune response can be triggered by DCs charged with either necrotic leukemic cell lysates or apoptotic leukemic cells or blebs (Galea-Lauri et al, 2002;Spisek et al, 2002;Weigel et al, 2006;Ruben et al, 2014). One plausible explanation for this observation is that the potential immunosuppressive effects of tumor cells can be overcome by the various immunostimulatory factors released from tumor cells upon necrotic or apoptotic cell death induction (Chiang et al, 2010).…”
Section: Reasonsmentioning
confidence: 99%
“…cyclophosphamide restores homeostasis of dendritic cells [46]. Attempts are also made to activate inborn immunity using such agents as TLR agonists [62], or vaccination with dendritic cells "loaded" with antigens isolated from patient's tumour [34,63]. This, in a restricted range, is used in the treatment [39,60].…”
Section: Description Of Principles In Tumour Treatment Taking Into Amentioning
confidence: 99%